Peningkatan Hasil Belajar Matematika melalui Model Problem Based Learning Berbantu Media Puzzle di Sekolah Dasar - Albi Meinisa; Wasitohadi Wasitohadi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to determine the improvement of mathematics learning outcomes of 5th grade students of SD Negeri Sidorejo Lor 01 Salatiga through a media puzzle assisted Problem Based Learning model. Problem Based Learning model which helped with puzzle to 5th grade students of SD Negeri Sidorejo Lor 01 Salatiga.The type of this research is Class Action Research (CAR) with a spiral model from C. Kemmis & Mc. Taggart. The research subjects were 5th grade students of SD Negeri Sidorejo Lor 1 Salatiga, totaling 36 students. Data collection techniques using test techniques in the form of evaluation and non-test questions in the form of observation and documentation. The results of the study were proven by the completeness of the 5th grade students learning at 47.2% pre-cycle, increased in the first cycle to 77.8%, and in the second cycle the students learning completeness reached 100% of 36 students. Thus it can be concluded that the learning mathematic using Problem Based Learning model which helped with puzzle can improve results of learning mathematic to 5th grade students of SD Negeri Sidorejo Lor 01 Salatiga.